Commentary on the Gospel of John - Theodorus Mopsuestenus 352-428 (Ancient Christian texts, 2010)
General introduction -- Translator's introduction -- Commentary on the Gospel of John -- Preface -- Book one (John 1:1; 2:22) -- Book two (John 2:23; 5:47) -- Book three (John 6:1; 8:59) -- Book four (John 9:1; 10:42) -- Book five (John 11:1; 12:50) -- Book six (John 13:1; 17:26) -- Book seven (John 18:1; 21:25)